2020
DOI: 10.3390/foods9070893
|View full text |Cite
|
Sign up to set email alerts
|

Design and Characterization of a Novel Fermented Beverage from Lentil Grains

Abstract: The experimental activities carried out in this study aimed at designing a lentil-based beverage rich in soluble and digestible proteins. In order to extract soluble proteins, lentil grains were soaked in water overnight, blended, treated with proteolytic enzymes and fermented with Lactobacillus strains. Protein enzymatic hydrolysis, carried out with four commercial food grade enzyme preparations, showed that bromelin, at the enzyme to substrate ratio of 10%, was the best solution to produce this novel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
39
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 45 publications
(45 citation statements)
references
References 45 publications
5
39
0
1
Order By: Relevance
“…In legumes, starch digestibility is much lower than that of cereal, which is ascribable to higher content of amylose in the former [ 69 ]. In this study, as already reported for other legume-based foods [ 8 , 21 , 70 ], fermentation with the selected lactic acid bacteria determined a considerable increase of resistant starch content, which is partially due to the acidification caused by the organic acids released during fermentation ( Table 2 ). Besides acidification, other food processing conditions (e.g., thermal treatments) can contribute to the resistant starch increase [ 69 ].…”
Section: Discussionsupporting
confidence: 82%
“…In legumes, starch digestibility is much lower than that of cereal, which is ascribable to higher content of amylose in the former [ 69 ]. In this study, as already reported for other legume-based foods [ 8 , 21 , 70 ], fermentation with the selected lactic acid bacteria determined a considerable increase of resistant starch content, which is partially due to the acidification caused by the organic acids released during fermentation ( Table 2 ). Besides acidification, other food processing conditions (e.g., thermal treatments) can contribute to the resistant starch increase [ 69 ].…”
Section: Discussionsupporting
confidence: 82%
“…p-Vinyl phenol is considered a food additive and is approved as a flavoring agent. Ethyl derivatives are considered the most important flavor components of fermented soy sauce, although they may cause off flavor in wine [68]. After fermentation, the phenolics profile in KLB that resulted was modified with respect to the unfermented mixture ( Figure 5).…”
Section: Effect Of Fermentation On Bioactive and Nutritional Compoundmentioning
confidence: 99%
“…After fermentation, KLB resulted in higher (p < 0.05) protein digestibility (94% ± 1%) with respect to the unfermented mixture (89% ± 1%). Recent developments in functional beverages focused on protein intake, since cereals and others plant matrices contain several compounds that can prevent protein digestibility [68,69]. Proteolysis operated by the endogenous enzymes as well by microbial enzymatic activities likely affected the in- After fermentation, KLB resulted in higher (p < 0.05) protein digestibility (94% ± 1%) with respect to the unfermented mixture (89% ± 1%).…”
Section: Effect Of Fermentation On Bioactive and Nutritional Compoundmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, although several efforts have been made, the major challenges still faced by producers of plant-based beverages and yogurt-like products are associated with the appearance and texture properties, unbalanced nutritional profile, and the presence of antinutritional compounds [1,[3][4][5]. Product stability is an important parameter of plant-based beverages and yogurt-like products in which particles can easily aggregate and precipitate resulting in serum separation [1,6].…”
mentioning
confidence: 99%